An integrated platform for fibrinogen quantification on a microfluidic paper-based analytical device. Issue 15 (26th June 2020) - Guan, Yanfang; Zhang, Kun; Xu, Fengqian; Guo, Ruiyang; Fang, Anshu; Sun, Baichuan; Meng, Xiangxin; Liu, Yansheng; Bai, Mingyang
Abstract : Fibrinogen (FIB) plays a key role in blood coagulation and thrombosis and its concentration in blood can directly reflect health conditions, thus an efficient detection of FIB would benefit the treatments of certain diseases such as liver and heart diseases. Abstract : Fibrinogen (FIB) plays a key role in blood coagulation and thrombosis and its concentration in blood can directly reflect health conditions, thus efficient detection of FIB would benefit the treatments of certain diseases such as liver and heart diseases. However, there is a lack of sensitive, simple, rapid and cheap FIB detection device currently, in lieu of expensive and sophisticated approaches in laboratories. Here, we propose a novel plasma separation and FIB detection platform based on a microfluidic paper-based analytical device (μPAD). It is the first time that dielectrophoretic (DEP) force is combined with capillary force on paper for plasma separation, and the separation efficiency of plasma reaches about 95%, ensuring reliable downstream FIB detection, for which we also propose a new method called the resistance-fibrinogen detection (RFD) method. It not only avoids the use of large-scale instruments for detection, but also possesses high precision and simplicity. The method is found to be reliable in FIB detection for various concentrations ranging from 127.0 to 508.0 mg dL −1 . Moreover, the results obtained from the proposed μPAD show an excellent agreement ( R 2 = 0.9985) with those obtained from an automatic coagulation analyzer with natural human blood samples. Overall, the proposed platform provides a low-cost and reliable approach for FIB detection, especially for clinical use in resource-limited areas.